Exploring millennials’ digital CSR communication expectations from Indonesian unicorn companies - Sherly Hindra Negoro; Nobertus Santoso (Faculty of Communications Science, Dr. Soetomo University, 2024)
Corporate Social Responsibility (CSR) communication is a conduit for companies to engage with the public. This research delves into millennials’ digital CSR communication expectations from Indonesian unicorn companies. Digital CSR initiatives aim to bridge the gap between corporate needs and public expectations. Public expectations encompass beliefs, attitudes, and anticipations. The study focuses on five Indonesian unicorn companies—Gojek, Tokopedia, OVO, Traveloka, and Bukalapak. Data collection involved interviews with millennials who follow the Instagram accounts of unicorn companies. Findings reveal diverse millennial expectations generated through CSR communication on Instagram, spanning visual message representation, media utilisation, and prospective CSR programs. Storytelling emerges as a pivotal method for conveying expectations via Instagram accounts. Moreover, Instagram is not the sole medium utilised for CSR communication. Follower interest underscores the necessity for sustained, long-term CSR programs. Positive engagement, such as likes, shares, and comments, represents a tangible manifestation of the millennials’ positive response to the content shared by these companies.